Interactive Learning Environment for Children in the Beliefs of Pre-School Teachers - Magdalena Grochowalska (Journal of Elementary Education, 2014)
The goal of the present paper is to examine the problem of determinants of the learning process in preschool children. The study presented the issue of support provided in the learning process with reference to teachers’ beliefs on education that help them undertake initiatives they find most effective. In the introduction the importance of the interaction in which children are involved for the learning process was presented. Subsequently, the way children function in a preschool learning environment was focused on, as described by female pre-school teachers. This article reports on an investigation into the reconstruction of the meaning that pre-school teachers attach to the support they give children in the course of their learning process.